2021
DOI: 10.1007/s00253-020-11084-y
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic identification, purification and characterisation of the Bifidobacterium adolescentis BgaC β-galactosidase

Abstract: Members of the human gut microbiota use glycoside hydrolase (GH) enzymes, such as β-galactosidases, to forage on host mucin glycans and dietary fibres. A human faecal metagenomic fosmid library was constructed and functionally screened to identify novel β-galactosidases. Out of the 16,000 clones screened, 30 β-galactosidase-positive clones were identified. The β-galactosidase gene found in the majority of the clones was BAD_1582 from Bifidobacterium adolescentis, subsequently named bgaC. This gene was cloned w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…As shown in Figure 4A, when p NPG was used as the substrate, the activity of BtGal42 was about 297.2% of that on o NPG, indicating that BtGal42 had a noticeable preference for the cleavage of β‐D‐anomeric linkages. This phenomenon was also observed for β‐galactosidases from B. adolescentis , 29 B. velezensis SW5, 41 and B. coagulans NL01 10 . No activity was detected when p NPαG, p NPGul, p NPLac, and p NPCel were used as substrates, indicating that BtGal42 acted exclusively on terminal β‐linked Gal residues.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…As shown in Figure 4A, when p NPG was used as the substrate, the activity of BtGal42 was about 297.2% of that on o NPG, indicating that BtGal42 had a noticeable preference for the cleavage of β‐D‐anomeric linkages. This phenomenon was also observed for β‐galactosidases from B. adolescentis , 29 B. velezensis SW5, 41 and B. coagulans NL01 10 . No activity was detected when p NPαG, p NPGul, p NPLac, and p NPCel were used as substrates, indicating that BtGal42 acted exclusively on terminal β‐linked Gal residues.…”
Section: Resultsmentioning
confidence: 66%
“…The activities of β‐galactosidase from B. velezensis SW5, 41 B. longum CCRC 15708, 46 and P. barengoltzii 30 were also inhibited by Ca 2+ . BtGal42 was completely inhibited by Cu 2+ , Zn 2+ , and Fe 3+ , as the most reported bacterial β‐galactosidases 27,29,30,41 . On the other hand, it was found that Mg 2+ enhanced the activity of BtGal42 by within 15%.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations